Medicine in an Age of Revolution - Elmer, Peter (Oxford University Press, 2023)
This work is the first major attempt since the 1970s to challenge the idea that the essential engine of medical (and scientific) change in seventeenth-century Britain emanated from puritanism. It seeks to reaffirm the crucial role of the period of the civil wars and their aftermath in providing the most congenial context for a re-evaluation of traditional attitudes to medicine. In the process, it rejects the idea that such initiatives were the special preserve of a small religious elite (puritans), claiming instead that enthusiasm for change can be found across the religious spectrum. At the same time, the work demonstrates that medical practitioners were increasingly drawn into contemporary religious and political debates in a way that led to a fundamental politicization of the 'profession'. By the end of the seventeenth century, it was now commonplace to see doctors, apothecaries and surgeons fully engaged in everyday political and civic life. At the same time, religious and political orientation often became an important factor in the career development of medics, especially in towns and cities, where substantial benefits might accrue to those who found themselves in favour with the ruling elites, be they Whig or Tory. The body politic, a Renaissance commonplace, was now peopled by medical practitioners who often claimed a special authority when it came to diagnosing the ills of late seventeenth-century society.